A cladistic approach to the evolution of steppe scripts. (22nd June 2022) - Puskás, Timea; Hosszú, Gábor
The paper deals with the cladistic modelling of the evolution of specific pattern systems, namely historical scripts. A pattern system is a specific form of symbolic communication consisting of symbols and syntactic rules. The evolutionary study of pattern systems is called pattern evolution. The main obstacle to phylogenetic modelling of historical scripts as special pattern systems is the small number of features, which means a high risk of homoplasies. Therefore, their evolution cannot be analysed directly using cladistic methods but only applying phenetic analysis in certain cases. Previous research extended the phenetic model with evolutionary considerations, and a successive elimination procedure was developed to avoid homoplasies. Thus, the resulting database is already suitable for cladistic analysis. The procedure described in this paper illustrates cladistic analysis performed this way. The end result is a most parsimonious cladogram illustrating the evolution of the scripts of the steppe peoples.